Isozyme studies of resistant and susceptible clones of Saccharum officinarum L. to fungal diseases - R. Rajendran, V. Natarajan, M. Anbazhagan, M. Kalpana (Journal of Ecobiotechnology, 2009)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-bidi-font-weight: bold; mso-bidi-font-style: italic; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Sugarcane is one of the important commercial crops of India and it plays an important role in maintaining the economy of the nation. Many diseases of sugarcane lead to loss of net productivity of sugar and by growing resistant varieties the loss can be reduced to considerable amount. Hence, in this study an attempt has been made to identify a resistant clone through isoenzyme analysis. Three resistant (Bo-91, Co-86249, Co-93009) and three susceptible (CoC-671, CoC-86032, CoC-92061) clones of Saccharum officianarum L. were selected for the study. In native-PAGE analysis (for peroxidase) distinct bands with Rf value 0.537 and 0.694 were observed in resistant clones, and the susceptible clones lack these bands.Ã‚Â  An increase in peroxidase activity is also observed in clones that possessed the distinct Rf values 0.537 and 0.694. From this, it can be concluded that the clones possessing distinct Rf values are resistants when compared to other clones as they are having high peroxidase action.